An Automated Approach for General Movement Assessment: A Pilot Study - Fontana, Camilla; Ottaviani, Valeria; Veneroni, Chiara; Sforza, Sofia E.; Pesenti, Nicola; Mosca, Fabio; Picciolini, Odoardo; Fumagalli, Monica; Dellacà, Raffaele L. (Frontiers in Pediatrics, 2021)
OBJECTIVE: To develop an automatic quantitative approach to identify infants with abnormal limbs’ movements at Term Equivalent Age (TEA) as compared to general movements assessment (GMA). METHODS: GMA was performed at TEA by a trained operator in neonates at neurological risk. GMs were classified as normal (N) or Abnormal (Ab), which included poor repertoire and cramped synchronized movements. The signals from four micro-accelerometers placed on all limbs were recorded for 10-min simultaneously. A global index (KC_index), quantifying the characteristics of individual limb movements and the coordination among limbs, was obtained by adding normalized kurtosis of the distribution of the first principal component of the acceleration signals to the cross-correlation of the jerk for the upper and lower limbs. RESULTS: Sixty-eight infants were studied. A KC_index cut-off of 201.5 (95%CI: 199.9–205.0) provided specificity=0.86 and sensitivity=0.88 in identifying infants with Ab movements. CONCLUSIONS: KC_index provides an automatic and quantitative measure that may allow the identification of infants who require further neurological evaluation.